(untitled) (MUZIKOLOGIJA-MUSICOLOGY, 2025)
Proceeding from the idea of the readymade, Marko Ristić’s, Vane Bor’s and Dušan Matić’s collages regroup readymade pictorial and textual matrices according to the rules of free associative syntax. Everything that they collected cut out and pasted bears the hallmark of personal choice, i.e. objective chance, as the Surrealists would say. In the new structure of the collage, picture and text were of equal importance. However, we should not forget that both picture and text were only fragments, of different origin so that they could not function as autonomous elements in their own right nor could they establish logical interlinks. Cut and paste picture in Surrealism are primarily registered as visual wholes, in which the former principle of harmony has been substituted by the principle of discontinuity. In fact, they do not aspire to establish closed and unambiguous semantic structures either on a single paper or within a cycle, disregarding as they do conventional narrative and illustrative order in representing reality.